Two new species of free-living nematodes genera Microlaimus de Man, 1880 and Aponema Jensen, 1978 (Nematoda: Microlaimidae) from the Black Sea - Revkova, Tatiana N. (Zootaxa, 2017)
Two new species of the family Microlaimidae Micoletzky, 1922 are described and illustrated from the Black Sea. Aponema pontica sp. n. is morphologically closest to A. torosum in the shape of the body and spicules, size of amphids, but differs in having small and triangular cardia, absence of constriction in head region, shape of gubernaculum apophyses, rounded and weakly sclerotised lumen of pharyngeal bulb and longer spicules. Microlaimus paraglobiceps sp. n. morphologically resembles M. globiceps de Man, 1880 in the shape of the body, structure of the male sexual organs and presence of precloacal pore, but the main difference is a shorter body, cuticle finely annulated all over the body and absence of sexual dimorphism in the size of amphideal fovea.